2016
DOI: 10.3389/fenvs.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Food Adulteration and Bio-Magnification of Environmental Contaminants: A Comprehensive Risk Framework for Bangladesh

Abstract: This article thoroughly investigates the severity of the prevailing environmental conditions and evaluates the resulting threats to food intake and public health in Bangladesh by establishing relationship among different contaminant transfer mechanisms to human. It describes the potential of certain contaminants to get bio-magnified through the food chain. A database was prepared on a number of contaminants in the study area that are responsible for rendering different foods vulnerable to produce long term or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Although the present investigation did not examine the effects of adulterants on imported apples, the screening system should be expanded to monitor and control their use on fruits, as there is evidence of adverse health effects associated with adulterants in the food industry. 77 Further studies are needed to continue to improve the database on food metal contents for comparative studies. Moreover, an analytical approach for As and Hg speciation in fruits is necessary for effective food safety assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present investigation did not examine the effects of adulterants on imported apples, the screening system should be expanded to monitor and control their use on fruits, as there is evidence of adverse health effects associated with adulterants in the food industry. 77 Further studies are needed to continue to improve the database on food metal contents for comparative studies. Moreover, an analytical approach for As and Hg speciation in fruits is necessary for effective food safety assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The concern is backed up by data. Researchers have found that more than half of the foods consumed in Dhaka city were either adulterated or contaminated with toxic compounds (DDTs, formalin, textile dyes) or harmful microorganisms [54][55][56], leaving Dhaka residents uncertain about the quality of the foods available. This situation and these ndings underscore the importance of ensuring that safe foods become the expected norm so that people can be encouraged to eat fruit and vegetables which are the basis of healthy diets.…”
Section: Discussionmentioning
confidence: 99%
“…Even more unfortunate is the fact that nefarious practice of food adulteration increases exponentially during the month of Ramadan in Bangladesh, according to a study of European Journal of Sustainable Development Research, 2019 [85] . The number of patients suffering from cancer, diabetes, and kidney diseases is on the rise due to food adulteration [86][87][88][89] . 6.5.…”
Section: Fatty and Fried Food After Religious Fastingmentioning
confidence: 99%